2015
DOI: 10.1088/0031-9155/60/17/6719
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the normal lung dose–response curve from clinical DVH data: a possible role for low dose hyper-radiosensitivity, increased radioresistance

Abstract: In conventionally fractionated radiation therapy for lung cancer, radiation pneumonitis’ (RP) dependence on the normal lung dose-volume histogram (DVH) is not well understood. Complication models alternatively make RP a function of a summary statistic, such as mean lung dose (MLD). This work searches over damage profiles, which quantify sub-volume damage as a function of dose. Profiles that achieve best RP predictive accuracy on a clinical dataset are hypothesized to approximate DVH dependence. Step function d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Dawe et al [ 6 ] reported that radiotherapy demonstrated unsatisfactory outcomes, with a median survival of 10 months and 5-year survival of only 5% in stage III NSCLC patients. Other studies have shown that the local recurrence rate of NSCLC could be up to 60-70% after conventionally fractionated radiotherapy [ 7 , 8 ]. Further, patients with radioresistant tumors are at high risk for recurrence and usually have very poor prognoses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dawe et al [ 6 ] reported that radiotherapy demonstrated unsatisfactory outcomes, with a median survival of 10 months and 5-year survival of only 5% in stage III NSCLC patients. Other studies have shown that the local recurrence rate of NSCLC could be up to 60-70% after conventionally fractionated radiotherapy [ 7 , 8 ]. Further, patients with radioresistant tumors are at high risk for recurrence and usually have very poor prognoses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radioresistance is a major bottleneck in the treatment of tumor and its relapse [4]. The local recurrence rate in NSCLC is up to 60–70 % in 2 years after conventional fractionated radiotherapy (CFRT) (60 Gy/30 F/6 W) [5, 6]. Therefore, it is very critical to enhance the radiosensitivity of lung cancer so as to reduce the relapse.…”
Section: Introductionmentioning
confidence: 99%
“…2.1. University of Michigan DVH data UM data is reported in detail by Kong [4] (see also prior publications cited by Kong), and has been previously analyzed in Gordon et al [8,9]. In summary, the UM dataset consists of 89 DVHs for total lung minus gross tumor volume.…”
Section: Methodsmentioning
confidence: 99%
“…Recent measurements [13,14] suggest that the α/β ratio for normal lung is lower than 3 Gy, motivating the value α/β=2 Gy. Based on Gordon et al [8] selected IRM model parameters are α s =0.04, α r =0.0032, D c =0.22, β=0.0032, and α r /β=1. The default assumption in this work is that the number of fractions N=30.…”
Section: Simulated Rp Datamentioning
confidence: 99%
See 1 more Smart Citation